The long shadow of accumulating adverse childhood experiences on mental health in the United Arab Emirates: implications for policy and practice - Murphy, Anthony; England, Dawn; Elbarazi, Iffat; Horen, Neal; Long, Toby; Ismail-Allouche, Zeina; Arafat, Cairo (Frontiers in Public Health, 2024)
Introduction This study investigates the cumulative effects of adverse childhood experiences (ACEs) on adult depression, anxiety, and stress in Abu Dhabi, controlling for demographic factors, lifestyle, and known health and mental health diagnoses. Methods Utilizing a cross-sectional design and self-report measures, the research aims to fill a critical gap in understanding the specific impacts of ACEs in the UAE. Based on a multi-site, cross-sectional community sample of 697 residents of Abu Dhabi. Results The findings reveal significant variances in current screening values for depression, anxiety, and stress attributable to ACEs after controlling for demographic factors, lifestyle risk factors, and adult diagnoses of health and mental health conditions. Discussion The results underline the lifelong impact of ACEs and reinforce the importance of early identification and intervention. In particular, the implications for policy and practice in understanding and mitigating ACEs long-term effects on mental health are considered.